Discovery of the Zimbabwe Ruins (Historia, 2021)
The    statement   by   "D.M.H." (Historia     Junior,    27,   August,    1963)that   the   Zimbabwe   Ruins   were   discovered   by   Adam   Renders   in   1868,cannot  be  sustained  in  the  face  of  evidence  from   early  accounts.One  of  the  few  substantially    correct  versions   in   English-  of  the   difj-~ovelY  is   by  Summers  in  a  recent  publication}Events  leading   to  the  discovery  might   well  be  summarised  here  morefully,   since  the  main  sources  are  evidently   not   readily   accessible to  thosewho  write   on  the  subject.During   the  first   three  years  after  his  arrival   in  the  Eastern  Transvaalin   April,     1860,  thc   Rev.  A.    Merensky    (father    of  Dr.   H.   Merensky   ofplatinum    and   diamond   fame)   heard   m~ny   stories   about   ruins   of   stonenorth   of  the  Limpopo. He  tried  to  obtain  more  information   from   elephanthunters  and  the  indigenous  people,  and  although  everyone  who  had  travelledin  the  north   knew  about  these  old   structures,  the  information    was  vague.2Among   Merensky's   informants    was  a   Lekwapa   (Shangaan),    namedMalema,  who  had  seen the  ruins  while   acting  as  a  bearer  to  a  Portuguesetrader,   but  he  was  afraid   to  venture  closely.3The  Rev.   Merensky  and  his   colleague,  the  Rev.   Nachtigal,   left   theirMission   Station   in   July,    1862,  to   reconnoitre    on   foot   the   land   to   thenorth,  setting  as their  ultimate  objective  the  Ruins  of Zimbabwe.    Merensky'sdetailed   report   of  this   ,journey,  evidently   compiled   from   a  diary   after  hisreturn,   is   quoted   by   Wangemann.4South-east  of   the   present  Tzaneen  they   obtained   from    Serobane,  alocal   chief,  the  services  of  Makeritsane,  to  guide  them  across the  Limpopoto  the  "ruins   of  old   buildings",    from   which  country  Makeritsane  emanated.On  reaching  the  Venda,  east of  the  present  Louis   Trichardt,   the  partyfound   the  people  suffering   from   small-pox,   and  also  learnt  that  there  wasno  epidemic-free   passage to  the  north. Reluctantly   they  abandoned  theirobjective,   and  returned   to   Sekukuniland,   where  Chief   Sekukuni  told   themof   extensive   ruins,   which   he  had   seen  in  the   country   they  had  intendedvisiting,    during    his   wanderings    with   his   fathel     (Sekwati)    as  fugitives(from   Mzilikazi).5When   the   German   traveller,    Karl    Mauch,   heard   about   these  ruinsfrom   Merensky   in   1867,  they  agreed  upon  a  joint    visit   to  the   legendaryold   buildings.
Keywords: Merensky, A; Ruins of Zimbabwe; Zimbabwe; Mauch; Zimbabwe ruins